1989
DOI: 10.1182/blood.v74.4.1360.bloodjournal7441360
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic significance of interleukin-6 (IL-6/BSF-2) in Castleman's disease

Abstract: Castleman's disease is a syndrome consisting of giant lymph node hyperplasia with plasma cell infiltration, fever, anemia, hypergammaglobulinemia, and an increase in the plasma level of acute phase proteins. It has been reported that clinical abnormalities disappear after the resection of the affected lymph nodes, suggesting that products of lymph nodes may cause such clinical abnormalities. Interleukin-6 (IL-6) is a cytokine inducing B-cell differentiation to immunoglobulin-producing cells and regulating bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
195
1
8

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(205 citation statements)
references
References 0 publications
1
195
1
8
Order By: Relevance
“…Several lines of evidence suggest that excess interleukin‐6 (IL‐6), a cytokine that promotes B cell and plasma cell growth, plays an important role in symptoms and disease progression in many iMCD patients . Anti‐IL‐6 monoclonal antibodies (mAb) tocilizumab (anti‐IL‐6 receptor) and siltuximab (anti‐IL‐6) have been approved for iMCD in various regions of the world .…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggest that excess interleukin‐6 (IL‐6), a cytokine that promotes B cell and plasma cell growth, plays an important role in symptoms and disease progression in many iMCD patients . Anti‐IL‐6 monoclonal antibodies (mAb) tocilizumab (anti‐IL‐6 receptor) and siltuximab (anti‐IL‐6) have been approved for iMCD in various regions of the world .…”
Section: Introductionmentioning
confidence: 99%
“…Overproduction of circulating cytokines has been implicated in the pathogenesis and symptomatology of CD [16] and its sister syndrome POEMS syndrome (peripheral neuropathy, organomegaly, endocrinopathy, monoclonal protein, and skin changes) [16–18]. Interleukin‐6 (IL‐6) is related to the pathogenesis of CD for many patients as shown by the following three observations: removal of CD mass causes an abrupt drop in IL‐6 levels and resolution of symptoms [19]; treatment with IL‐6 receptor antibody relieves the symptoms and signs [20, 21]; overexpression of IL‐6 in mice produces a phenotype similar to the multicentric CD phenotype [22].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, and before considering the diagnosis of CD, a number of associated diseases that can exhibit Castleman‐like features on lymph node biopsy, should be ruled out, while some autoimmune diseases may actually be considered as true complications of CD. In most cases of MCD, interleukin‐6 (IL6), either human IL6 in iMCD or viral IL6 in HHV‐8+ MCD, plays a major role in the pathophysiology of the clinical and biological symptoms of the disease (Yoshizaki et al , ; Brandt et al , ; Oksenhendler et al , ; Uldrick et al , ). Therefore the IL6 pathway has been considered as a major target for therapy in iMCD (Nishimoto et al , ; van Rhee et al , ), whereas targeting B cells with rituximab has been shown to be very effective in HHV‐8+ MCD (Bower et al , ; Gérard et al , ).…”
mentioning
confidence: 99%